2014
DOI: 10.3329/bjp.v9i2.18831
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and related issues: An overview of Bangladesh situation

Abstract: The present study was designed to understand Bangladesh situation about antimicrobial resistance. Half of the Escherichia coli, Staphylococcus aureus, Pseudomonas and Klebsiella showed resistance against older and common antimicrobials. Most (50%) common reasons to prescribe antimicrobial are fever, respiratory and urinary tract infection. About 70% prescriber mentioned diagnostic uncertainty and emergence of resistance as causes for increase in antimicrobial prescribing. 51.9% of prescribers opined that physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 9 publications
2
32
0
Order By: Relevance
“…This is supported by the fact that prescribers choose cephalosporin antibiotics to avoid patients' risk of failure to low spectrum antibiotic prescription in RTIs in Bangladesh. 10 The higher cephalosporin resistance (67%) in the present study were similar with the data of cephalosporin resistance among E. coli isolates in Pakistan (90%), India (83%) and Russia (77%). 16 100% sensitivity of E. coli isolates to carbapenem antibiotics observed in this study however, in India, 11% of 408 isolates were resistant against them.…”
Section: Antibiotic Resistance Pattern Of Rti Patientssupporting
confidence: 79%
See 1 more Smart Citation
“…This is supported by the fact that prescribers choose cephalosporin antibiotics to avoid patients' risk of failure to low spectrum antibiotic prescription in RTIs in Bangladesh. 10 The higher cephalosporin resistance (67%) in the present study were similar with the data of cephalosporin resistance among E. coli isolates in Pakistan (90%), India (83%) and Russia (77%). 16 100% sensitivity of E. coli isolates to carbapenem antibiotics observed in this study however, in India, 11% of 408 isolates were resistant against them.…”
Section: Antibiotic Resistance Pattern Of Rti Patientssupporting
confidence: 79%
“…9,10 Moreover, context and disease-specific surveillance data of antimicrobial sensitivity are limited in Bangladesh, 10 although this information has paramount importance to develop local and national antibiotic guidelines. RTIs specific antibiotic guidelines are very important in this context to reduce over and imprudent prescription of antibiotics by prescribers at all levels from primary to tertiary care.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, research findings are usually not translated into clinical practice in Bangladesh as revealed in different previously conducted studies (Khatun et al, 2008;Rahman and Huda, 2014;Afreen and Rahman, 2014). The present undergraduate and postgraduate medical education programs are not responsive or accommodative to newer research findings and approaches (Rahman, 1995;Begum et al, 1999;Rahman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Print (0.02-2.0%) and electronic media (0.0-0.6%) attaches insignificant importance on the AMDR. Antimicrobials and strategy to fight against microbial resistance were not at all talked in the official papers of health and allied science [111]. Another study long before commented that pharmacology teaching and assessment system in 5 year MBBS program neither reflect community need or course objectives [112].…”
Section: The People's Republic Of Bangladeshmentioning
confidence: 99%